KURIKULUM DAN METODE PEMBELAJARAN PONDOK PESANTREN DARUL AMAL KERTAHARJA PEDES KABUPATEN KARAWANG - Siti Monica Khoirunnisa; Amirudin Amirudin; Iqbal Amar Muzaki (Universitas Islam Madura, 2022)
This research is entitled curriculum and learning methods at Darul Amal Islamic Boarding School. This study aims to determine the curriculum and methods used, steps for applying the method, supporting factors and inhibiting factors at Darul Amal Islamic Boarding School. This research is a qualitative research, because the research process is carried out based on natural phenomena or phenomena. The data collection technique used in this research is observation or coming directly to the field and also interviews with the owner and Ustadz/Teacher at Darul Amal Islamic Boarding School. Data analysis is done by systematically collecting and compiling the results of data obtained from observations and interviews and then organizing them into categories, synthesizing, choosing which ones are important and will be studied and then making conclusions so that they are easily understood by themselves and others. The results showed that the learning methods used at Darul Amal Islamic Boarding School were sorogan and memorization. As for the programs that are run such as Muhadastah, Muhadharah, Wetonan etc. Darul Amal Islamic Boarding School has several extracurricular activities, namely Martial Arts, Scouts, Calligraphy, Marawis etc. The expected targets for students are 1 year of memorizing Juz 'Amma, 6 months of memorizing Surah Yaasiin and Short Surahs, and 4 months of being able to Read and Write the Qur'an.